Research on Innovation and CSR of Small and Medium Textile Machinery Enterprises - Liu, Yubing (International Journal of Global Economics and Management, 2024)
This study focuses on small and medium-sized textile machinery enterprises in China, exploring how they can optimize sales performance through innovation and corporate social responsibility (CSR) practices, combined with organic online traffic and word-of-mouth recommendation strategies. Amidst the backdrop of fierce global competition in the textile industry, shifting consumer preferences, and heightened environmental requirements, the COVID-19 pandemic and Sino-American trade conflict have further exacerbated challenges faced by the industry. As a crucial link in the textile supply chain, textile machinery enterprises have also been impacted. Despite these difficulties, small and medium-sized textile machinery enterprises play a significant role in industry development and competitiveness. By integrating modern marketing strategies with CSR practices, this study aims to reveal how enterprises can effectively communicate their CSR commitments to expand market influence, boost sales growth, and strengthen brand reputation. The findings indicate that innovation and CSR play a pivotal role in enhancing corporate competitiveness, differentiating from competitors, and fostering brand loyalty. Based on interviews with a family-owned enterprise, this study observes that while the enterprise has achieved notable success in CSR practices, there is room for improvement in its marketing and communication strategies. Therefore, this paper proposes improvements such as optimizing the official website to highlight CSR, increasing investment in social media marketing, and combining CSR with offline word-of-mouth recommendations, with the aim of helping enterprises more effectively convey their CSR philosophies, attract potential customers, and drive sustained business growth.